2016
DOI: 10.2196/humanfactors.4853
|View full text |Cite
|
Sign up to set email alerts
|

Using the NIATx Model to Implement User-Centered Design of Technology for Older Adults

Abstract: What models can effectively guide the creation of eHealth and mHealth technologies? This paper describes the use of the NIATx model as a framework for the user-centered design of a new technology for older adults. The NIATx model is a simple framework of process improvement based on the following principles derived from an analysis of decades of research from various industries about why some projects fail and others succeed: (1) Understand and involve the customer; (2) fix key problems; (3) pick an influentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Older adults comprise an increasing proportion of the US population. One way for technology companies to increase adoption of mobile phones for older adults is to include them in participatory design and usability testing [62,63]. Adapting devices and tailoring online advanced features to meet the needs of older homeless adults could facilitate their inclusion in the digital economy.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults comprise an increasing proportion of the US population. One way for technology companies to increase adoption of mobile phones for older adults is to include them in participatory design and usability testing [62,63]. Adapting devices and tailoring online advanced features to meet the needs of older homeless adults could facilitate their inclusion in the digital economy.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in delays and some instances of redesigning elements of Engage that should have been tested with end-users prior to the usability evaluation phase. Even when an agile approach is not explicitly used, there are good examples of rapid-cycle testing of CHIT that have avoided the time delays experienced in the present study (e.g., Gustafson Jr. et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“… 13 29 30 However, more recently, progress has been made in the development of eHealth applications suitable for the elderly. 31 Studies have shown that eHealth can be used by older patients, without difficulties, for example, by older men with prostate cancer. 32 Furthermore, the interviewed GPs considered poorly educated patients not capable of understanding the feedback and personalised advice on their reported outcomes in Oncokompas 2.0 .…”
Section: Discussionmentioning
confidence: 99%